School Counselors' Persuasive Communication in Shaping Students' Character at SMAN 38 Jakarta - Selamat Ginting; Nuriyati Samatan; Daryani Daryani; Agus Salim (Green Publisher, 2026)
Guidance and Counseling (BK) teachers are one of the essential elements in student development across almost all school levels in Indonesia. BK teachers serve as